Association between perceived noise at work and mental health among employed adults in Southwest China - Yang, Shujuan; Fu, Yao; Dong, Shu; Yang, Bo; Li, Zhitao; Feng, Chuanteng; Reinhardt, Jan D.; Shi, Wei; Jia, Peng; Zeng, Honglian; Yu, Bin (Journal of affective disorders, 2023)
Perceived noise at work may contribute more to worsening mental health than objectively measured noise. However, evidence regarding this association is scarce. We investigated the associations of perceived noise at work with anxiety and depression and identified vulnerable subpopulations. Data from 28,661 participants of the Chinese Cohort of Working Adults (CCWA) were analyzed. Logistic or multinomial logistic regression models were used to determine associations between perceived noise at work and the severity of probable anxiety, depression, and their comorbidity. The generalized additive model with restricted cubic splines was applied to estimate the non-linear trend of associations. The mean age of participants was 36.55 ± 10.42 years. We observed that a higher level of perceived noise at work was associated with a higher risk of severe anxiety (OR = 1.55. 95%CI: 1.51–1.59) and severe depression (OR = 1.77. 95%CI: 1.72–1.84). More perceived noise at work was further associated with increased odds of comorbid anxiety and depression (OR = 1.28, 95%CI: 1.26–1.30). We observed an approximately J-shaped curve for the association between perceived noise at work with anxiety, depression, and their comorbidity. Participants, who were male, aged <45 years, had high education levels, and worked on trains were characterized by a greater impact of perceived noise at work on mental health problems. Increased perceived noise at work was associated with an elevated risk of anxiety, depression, and their comorbidity. These associations were moderated by sex, age, education level and occupation. Interventions targeting perceived noise at work may promote employed adults' mental health. •Perceived noise at work may contribute to a larger degree to worsening mental health than objectively measured noise while receives less attention.•Increased perceived noise at work was associated with an elevated risk of anxiety, depression, and their comorbidity.•We observe an approximately J-shaped curve for the association between perceived noise at work with anxiety, depression, and their comorbidity.•The association between perceived noise at work and mental health was moderated by sex, age, education level, and occupation, suggesting individual differences in noise sensitivity and psychological adaptability.